Roles and Responsibilities of Notary in Making the Results Agreement of Criminal Sanctions - Husni Basya; Dwi Kurniawan; Sri Endah Wahyuningsih (Jurnal Akta, 2018)
Notary institutions emerge from the growing needs of society today. Which requires evidence of the relationship existing civil law and / or between them, the general rule as to where and when the law demands it or it is desired by the community, to make written evidence that has authentic power. On 16 June 1925, out instructions to the Notary who practice in Indonesia, instruction, which contains 10 articles containing provisions that a Public notary before the first practice was sworn in. Notary Oath become a necessity of Principles of Public Law (Publiek Rechtelijk Beginsel): "That a public official before running its position as legally must take the oath first, if not it is not legitimate to run its position despite being lifted. "Oath Notary at Notary Act No. 2 of 2014 provided for in Article 4 to Article 7, while Article 17 Regulation of the contents oath Notary amended by Regulation No. 11 of 1949 has been repealed with the enactment UUJN. In the UUJN article 1, paragraph 1 Notary is a public official authorized to make an authentic agreement and other authorities referred to in this Act. Agreement of Notary must have the strength of evidence was authentic anyway, because according to article 1870 of the Civil Code authentic agreement must give them the parties and their heirs or persons who have the right of them a perfect evidence about what is contained in the agreement that the force formal and substantive evidence.Keywords: History of Notaries; Notary Oath; Criminal Sanctions.